Burnout as a Selected Aspect Affecting the Work Performance of a Social Worker - Lenka Lachytová; Peter Kalanin (Vasyl Stefanyk Precarpathian National University, 2016)
The aim of the empirical study is to identify the symptoms and the preventive measures of social workers' burnout, according to correlations of age, level of education, professional experience, length and the site of occupation. Design study. The study was carried out (from February to May 2016) on 49 respondents, social workers, by deliberate choice of typology: former colleagues currently working in NGOs of Košice and Prešov regions, with who we had participated in various projects providing general-utility services. The Inventory of Burnout Symptom by T. and J. Tošner was used for processing the collected data. The completion of this study is the correct implementation of innovative advanced technologies forming a part of the culture of the organization with clearly named functions and duties of the individual members of the working team.